2008
DOI: 10.1111/j.1742-4658.2008.06621.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative biochemical and structural analysis of the intracellular chorismate mutase (Rv0948c) from Mycobacterium tuberculosis H37Rv and the secreted chorismate mutase (y2828) from Yersinia pestis

Abstract: The Rv0948c gene from Mycobacterium tuberculosis H37Rv encodes a 90 amino acid protein as the natural gene product with chorismate mutase (CM) activity. The protein, 90‐MtCM, exhibits Michaelis–Menten kinetics with a kcat of 5.5 ± 0.2 s−1 and a Km of 1500 ± 100 μm at 37 °C and pH 7.5. The 2.0 Å X‐ray structure shows that 90‐MtCM is an all α‐helical homodimer (Protein Data Bank ID: 2QBV) with the topology of Escherichia coli CM (EcCM), and that both protomers contribute to each catalytic site. Superimposition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 35 publications
3
43
0
Order By: Relevance
“…Because no significant conformational change of the protein is observed on inhibitor binding, except in the near vicinity of the Phe binding site, inhibition of MtuDAH7PS is consistent with a change in protein dynamics, causing altered substrate binding (12). The genome of M. tuberculosis encodes two CM proteins (13,14). One is highly active and secreted into the periplasmic compartment, and its biological role is yet to be determined (14).…”
mentioning
confidence: 96%
“…Because no significant conformational change of the protein is observed on inhibitor binding, except in the near vicinity of the Phe binding site, inhibition of MtuDAH7PS is consistent with a change in protein dynamics, causing altered substrate binding (12). The genome of M. tuberculosis encodes two CM proteins (13,14). One is highly active and secreted into the periplasmic compartment, and its biological role is yet to be determined (14).…”
mentioning
confidence: 96%
“…1D), and similarly in chain C, and chain D. The citrate molecule also makes additional interactions with the residues Arg27, Arg50 and Phe79 via water bridge formation. It has been previously reported that the citrate inhibits the 90- Mt CM protein 34 .…”
Section: Resultsmentioning
confidence: 93%
“…Residues Phe57′, Ala59′ and Leu115 are also part of the active site 34 . The Bs CM_2 active site consists of similar residues.…”
Section: Resultsmentioning
confidence: 99%
“…Samples were processed for ZN staining before and after Decontamination of the sample with NALC-NaOH method. [6] Samples were processed for two molecular methods Line Probe Assay (LiPA), [7] (Hain Life sciences GmbH, Nerhren, Germany) and Sanger Sequencing (3130 genetic analyzer, Applied Biosystems) [8]. Study was done on monodrug and multidrug resistant strains of MTB complex.…”
Section: Introductionmentioning
confidence: 99%